Trimethylamine N-Oxide Was Not Associated With 30-Day Left Ventricular Systolic Dysfunction in Patients With a First Anterior ST-Segment Elevation Myocardial Infarction After Primary Revascularization: A Sub-analysis From an Optical Coherence Tomography Registry - Zhou, Jinying; Yu, Shiqin; Tan, Yu; Zhou, Peng; Liu, Chen; Sheng, Zhaoxue; Li, Jiannan; Chen, Runzhen; Zhao, Shihua; Yan, Hongbing (Frontiers in Cardiovascular Medicine, 2020)
Objective Left ventricular systolic dysfunction (LVSD) after ST-segment elevation myocardial infarction (STEMI) is associated with poor outcome. Trimethylamine N-oxide (TMAO), a gut metabolite, is linked to cardiovascular diseases but its relationship with LVSD after STEMI remains unclear. The present study therefore aimed to investigate the relationship between TMAO and LVSD at 30 days after a first anterior STEMI. Methods This was a sub-study from the OCTAMI (Optical Coherence Tomography Examination in Acute Myocardial Infarction) registry. Eligible patients were included in current study if they: 1) presented with a first anterior STEMI; 2) had available baseline TMAO concentration; 3) completed a cardiovascular magnetic resonance examination at 30 days after STEMI. LVSD was defined as left ventricular ejection fraction <50%. Associations between TMAO and left ventricular ejection fraction, infarct size and left ventricular global strain were examined. Results In total, 78 patients were included in final analysis. Overall, TMAO was moderately associated with peak cTnI (r=0.27, p=0.01), age (r=0.34, p<0.01), and estimated glomerular filtration rate (r=-0.30, p<0.01). At 30-day follow-up, 41 patients were in the LVSD group and 37 in the non-LVSD group. Baseline TMAO levels were not significantly different between the two groups (LVSD vs non-LVSD: median 1.9uM, 25th-75th percentiles 1.5uM -3.3uM vs median 1.9uM, 25th -75th percentiles 1.5uM-2.7uM; p=0.456). Linear regression analyses showed that TMAO was not associated with left ventricular ejection fraction, infarct size or left ventricular global strain at 30 days (all p>0.05). Conclusions TMAO was not significantly correlated with 30-day LVSD in patients with a first anterior STEMI after primary revascularization. Trial registration: url: https://clinicaltrials.gov/ct2/show/NCT03593928, NCT03593928, retrospectively registered.